Gendered situations, gendered selves a gender lens on social psychology - Howard, Judith A. 1947 August 4-; Hollander, Jocelyn A. (Thousand Oaks, California Sage Publications, Inc., 1997)
Social psychologists have often assumed that situations and behavior are gender neutral, yet assumptions about gender have affected the questions they have posed as well as the answers they have provided. Gendered situations, gendered selves is the second volume in the new Gender lens series--a groundbreaking series that looks at the complex and fascinating role of gender within our social world. Authors Judith A. Howard and Jocelyn A. Hollander explore the ways in which social psychology has simultaneously ignored and been deeply influenced by gender--carefully noting that gender differences are not the same as sex differences. Also discussed are the approaches to gender in social psychology research; how social psychology theories have been shaped by assumptions about gender, race, class, and sexuality; and the way gender influences identity and interaction. The mission of the Gender lens series is to unpack the assumptions about gender that pervade social life, and to examine the centrality of the assumptions about the way we perceive and interpret our world. Gendered situations, gender selves is an ideal introduction to the discussion of gender in social psychology, and will be useful in sociology and gender studies courses.
Defining social psychology and gender. What is social psychology? Social psychological theories. What is gender? Cross-cutting social positions. A gender lens -- Conceptions of gender in social psychology. Essentialist approaches, socialization approaches, social construction approaches, structural approaches -- Social exchange and related theories. Behaviorism, social learning theory, social exchange theory -- Social cognition. The organization of thought. Thinking : processing information. Constructing gender : behavior and cognition. Social cognition on gender -- Symbolic interactionism. The tools of symbolic interactionism. Who are we? Self and identity -- Gendered selves and identities. Presenting selves in interaction. Interactional repairs. Self-presentation and social structure. Resistance and negotiation -- Altruism and aggression : gendered dynamics of helping and harming others. Definitions. Social psychological explanations of altruism and aggression. Structural patterns of helping and aggression. Coda : helping and harming --. Lessons from opposition -- Reprising a gender lens on social psychology. A case in point. Traces of social psychological theories. Approaches to gender. Final messages for the reader.
Includes bibliographical references (pages 160-185) and indexes.
Keywords: Social psychology; Sex role; Personality and situation; Social exchange; Symbolic interactionism; Social perception